Pengaruh Penerapan Ketentuan Special and Differential Treatment dalam World Trade Organization Terhadap Pembangunan dan Perdagangan Internasional - Hasanie, Annisa; Sipahutar, Bernard (Faculty of Law, Universitas Jambi, 2020)
Abstract Globalization and liberalization have caused many economic actors from developing countries to be eliminated because they cannot compete with economic actors from developed countries. Developing countries are increasingly dependent on developed countries and international economic institutions such as the IMF and World Bank. The World Trade Organization as a world trade organization pays special attention to the interests of developing countries through the provisions of Special and Differential Treatment (S&D). Developing countries under certain conditions can be given special treatment that is more beneficial in their trade relations with developed countries. However, the provisions of S&D to date are still unfair and have a significant impact on the development progress of developing countries as expected. If seen based on MDGs Report data, many developing countries are still in a low level of economic prosperity.